2021
DOI: 10.1002/lt.25981
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis Is Associated With High Mortality and Readmissions Over 90 Days Regardless of COVID‐19: A Multicenter Cohort

Abstract: The short-term prognosis of coronavirus disease 2019 (COVID-19) is impacted by underlying cirrhosis and other comorbidities. (1) However, as shown in our multicenter study, inpatient mortality was similar in patients with cirrhosis + COVID-19 and cirrhosis without COVID-19, but was higher than a contemporaneous cohort of hospitalized patients with COVID-19 without cirrhosis. (2) We herein describe the 90-day postdischarge outcomes in that age-matched and sexmatched cohort of patients admitted with cirrhosis + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 3 publications
(7 reference statements)
4
17
0
7
Order By: Relevance
“…People with HIV, 17 and those who had a history of severe clinical manifestations of an infectious disease, including tuberculosis, 18 also showed a significant association with the severity of COVID-19. Additionally, and according to other studies, we found that diseases of the neurological system (eg, epilepsy, recurrent seizures 19 and Parkinson disease and parkinsonism 20 ), of the gastrointestinal tract (eg, liver cirrhosis and other liver chronic diseases 21 ), of metabolism (eg, gout 22 ), of the skin (eg, psoriasis 23 ), and of the blood and blood-forming organs (eg, coagulation defects 24 and anaemias 25 ) contributed to the COVID-19related clinical frailty. We also confirmed the involvement in a greater risk of severe or lethal forms of COVID-19 of mental disorders, such as psychosis and depression 26 as well as of recent dispensations of drugs with immunosuppressive properties (eg, corticosteroids 27 ), agents against chronic pain (eg, narcotic analgesics 28 ) or with an anticoagulant 29 action.…”
Section: Discussionsupporting
confidence: 81%
“…People with HIV, 17 and those who had a history of severe clinical manifestations of an infectious disease, including tuberculosis, 18 also showed a significant association with the severity of COVID-19. Additionally, and according to other studies, we found that diseases of the neurological system (eg, epilepsy, recurrent seizures 19 and Parkinson disease and parkinsonism 20 ), of the gastrointestinal tract (eg, liver cirrhosis and other liver chronic diseases 21 ), of metabolism (eg, gout 22 ), of the skin (eg, psoriasis 23 ), and of the blood and blood-forming organs (eg, coagulation defects 24 and anaemias 25 ) contributed to the COVID-19related clinical frailty. We also confirmed the involvement in a greater risk of severe or lethal forms of COVID-19 of mental disorders, such as psychosis and depression 26 as well as of recent dispensations of drugs with immunosuppressive properties (eg, corticosteroids 27 ), agents against chronic pain (eg, narcotic analgesics 28 ) or with an anticoagulant 29 action.…”
Section: Discussionsupporting
confidence: 81%
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…Hospital readmissions as a public health concern increase resource utilization and impose an additional burden on the healthcare system [ [9] , [10] , [11] ]. At the beginning of the pandemic, studies indicated that recurrence/re-infection of COVID-19 was rare [ 12 , 13 ], but more recent evidence has shown that a significant percentage of patients with COVID-19 develop recurrence of symptoms and require readmission [ 11 , 14 , 15 ]. The prevalence of hospital readmissions in patients with COVID-19 varies between 1% [ 16 ] to 48% [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the above-mentioned pro-inflammatory state may play a role for the decompensation of a stable disease. It has been proposed that neuro-hormonal activation, inflammatory activation and oxidative stress may have a primary role in the progression of a stable/chronic disease, mostly in acute heart failure or decompensated cirrhosis [15,16]. These complications may not be associated only with SARS-CoV-2 infection but also with its indirect medical effects on the healthcare system [17].…”
Section: Discussionmentioning
confidence: 99%